P74 Experiences of a simulated pleural biopsy training course for respiratory registrars in a high tuberculosis incidence region of the UK. (14th November 2013) - Ricketts, WM; Farrugia, M; Goldring, J; O'Shaughnessy, T; Sheaff, M; McLeod, DT
Abstract : Introduction and Objectives: Last year we presented data highlighting the on-going role for Abrams pleural biopsy in areas with high tuberculosis incidence (1). Feedback reiterated on-going need, but highlighted concerns regarding the attainment of trainee competence at this infrequently performed procedure. We organised and evaluated a half day training course using a well validated porcine-resin model at a regional registrar training day (2). Methods: All attendees (18) underwent a practical training session on pleural biopsy using Abrams and Tru-Cut biopsy needles. Feedback forms were completed and perceived success documented, all samples obtained underwent histological assessment by a specialist respiratory Consultant Histopathologist. Results: Previous experience was limited (median 0.5 prior biopsies performed, range 0–50). On Likert scales (range 1–5) mean confidence improved (1.86, SD 1.21 to 3.83, SD 0.51; p < 0.0001) and the session was deemed useful (mean score 4.5, SD 0.4) with 13/14 (92.9%) trainees who answered stating the session would change their practice. A mean of 4.56 samples (SD 1.42) were obtained per trainee. Sixty-nine of seventy-six samples (90.8%) were perceived to have been successful by the operator, microscopic evidence of mesothelial lined pleura was obtained in nine samples (11.8%) with connective tissue suggestive of possible pleura obtained in a further 25 (33%) (κ = 0.013; poor correlation); real time observation by a training partner suggested a 91.9% success rate (κ = 0.584; moderate correlation). There was no increase in accuracy with increased sampling. Despite encouragement only four participants attempted the Tru-Cut method. Conclusions: The session was popular and significantly improved trainee confidence. However, histological biopsy success rate and macroscopic correlation was poor. This is most likely related to difficulty in biopsying non-diseased pleura and possibly differences between macroscopic appearances of porcine and human pleura or inexperienced trainees' inability to recognise pleura macroscopically. Experience was low even in a high-incidence region, suggesting simulated pleural biopsy training may be a useful adjunct. References: Brown J et al . Abrams-Needle Pleural Biopsy Remains a Useful Investigation in Suspected Pleural Tuberculosis. Thorax 2012;67(Suppl 2):A113–A113. Naicker TR et al. Validation of a novel resin-porcine thorax model for chest drain insertion training. Clinical medicine 2012;12:49–52.